UKURAN KOMITE KOMITE AUDIT DAN PENERAPAN MANAJEMEN RISIKO - Pertiwi, Dinal Eka; Husaini, Husaini (JURNAL FAIRNESS, 2017)
This study aims to analyze the effect of the characteristics of the Audit Committee on the implementation of risk management. The intended characteristics of the Audit Committee are independence, expertise, size, and meetings. This study also uses company size, leverage, and auditor reputation as control variables.The sample in this study were non-financial companies listed on the Indonesia Stock Exchange in 2010-2011. Using the purposive sampling method, finally obtained 214 observations. This study uses logistic regression to analyze data.The results showed that the size of the audit committee had a positive and significant effect on risk management, while independence, meetings, competence had no influence on the implementation of risk management.